[Afisz. Incipit] Program Tygodnia A.Z.S. na Wybrzeżu ... (Gdańsk : [wydawca nieznany], 1950)
Afisz z programem imprez sportowych w dniach 23-29.04.1950 r.
Keywords: Sport -- Polska -- 1945-1970 -- druki ulotne; Sport -- Polska -- Gdańsk -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Druki ulotne -- 1945-1970.